A new disjunctive literal insertion fault detection strategy in boolean specifications. Issue 5 (16th February 2021) - Paul, T. K.; Chowdhury, M. J. M.; Lau, M. F.
Abstract: In fault‐based Boolean expression testing, the main challenge is to generate effective test cases that can detect faults within expressions. Previous studies show that it is hard to detect literal insertion faults, more specifically Disjunctive literal insertion fault (LIF[+]) compared with other faults in Boolean expressions. Researchers have been using different strategies such as multiple near false point coverage (MNFP) and modified condition decision coverage (MCDC) to detect LIF[+] faults. However, these strategies have their own limitations. For example, MNFP can only be applied when the expression is in irredundant disjunctive normal form (IDNF), and MCDC detects a low percentage of LIF[+] faults. In this paper, we propose an abstract syntax tree (AST)‐based test case generation strategy for LIF[+] fault detection that overcomes these limitations. Furthermore, our experimental results indicate that, on average, the test suites satisfying the proposed strategy can detect approximately 97.3% of LIF[+] faults for general form expressions and 89.7% of LIF[+] faults for IDNF expressions, which are 15.6% and 13.8% improvement, respectively, compared to the MCDC test suites. Moreover, the size of the required test suite is smaller than that of MCDC test suite. Abstract : This paper has presented a new test case selection strategy (namely, SFPC), to detect disjunctive literal insertion fault (LIF[+]) in Boolean expressions. The experimental results show that SFPC has detected approximately 97.3% of LIF[+] faulty expressions whereas UCM MCDC has detected 15.6% lower. In addition, for IDNF expressions, UCM MCDC has detected only 76.0% of LIF[+] faulty expressions whereas SFPC has detected 13.8% higher.